95. A computerized static posturography protocol in the assessment of balance impairment of Multiple Sclerosis patients. Issue 4 (April 2016) - Melillo, F.; Di Sapio, A.; Malentacchi, M.; Malucchi, S.; Capobianco, M.; Troni, W.; Bertolotto, A.
Abstract : Balance impairment is common in Multiple Sclerosis (MS) patients. We administered the modified Clinical Test of Sensory Interaction on Balance (mCTSIB) to 73 MS patients and 57 healthy controls, with the aim to collect normative data and compare sensitivity of mCTSIB and clinical examination in detecting balance impairment. Subjects were asked to stand quietly upright for 10 s with eyes opened and then eyes closed (EC) (3 times per condition) on a firm surface on a fixed dual forceplate. The centre of gravity (COG) sway was expressed as velocity (deg/s) and path length (mm); MS patients were examined with the Romberg Test (RT), scored according to Neurostatus. mCTSIB-EC clearly allowed to differentiate patients with positive RT (0.38 deg/s, CI 0.32–0.43) from those with negative RT (0.19 deg/s, 95% CI 0.17–0.21, p < 0.001). ROC analysis identified a cut-off value of 0.5 deg/s to define "positivity" to the mCTSIB (sensitivity 100%, specificity 95%, PPV 82%, NPV 100%). mCTSIB detected balance impairment in 19 MS patients (10 with negative RT). Compared to RT, the computerized posturographic test is more sensitive in detecting balance impairment in MS patients. It is easy to perform, fast to administer, not operator-dependent and provides objective data on postural control.